Evolution of the North Pacific Subtropical Mode Water in Anticyclonic Eddies. Issue 12 (26th December 2017) - Xu, Lixiao; Xie, Shang‐Ping; Liu, Qinyu; Liu, Cong; Li, Peiliang; Lin, Xiaopei
Abstract: Anticyclonic eddies (AEs) trap and transport the North Pacific subtropical mode water (STMW), but the evolution of the STMW trapped in AEs has not been fully studied due to the lack of eddy‐tracking subsurface observations. Here we analyze profiles from special‐designed Argo floats that follow two STMW‐trapping AEs for more than a year. The enhanced daily sampling by these Argo floats swirling around the eddies enables an unprecedented investigation into the structure and evolution of the trapped STMW. In the AEs, the upper (lower) thermocline domes up (concaves downward), and this lens‐shaped double thermocline encompasses the thick STMW within the eddy core. The lighter STMW (25.0 ∼ 25.2 σθ ) trapped in AEs dissipates quickly after the formation in winter because of the deepening seasonal thermocline, but the denser STMW (25.2 ∼ 25.4 σθ ) remains largely unchanged except when the AE passes across the Izu Ridge. The enhanced diapycnal mixing over the ridge weakens the denser STMW appreciably. While many AEs decay upon hitting the ridge, some pass through a bathymetric gap between the Hachijojima and Bonin Islands, forming a cross‐ridge pathway for STMW transport. By contrast, the North Pacific Intermediate Water (NPIW) underneath is deeper than the eddy trapping depth (600 m), and hence left behind east of the Izu Ridge. In Argo climatology, the shallow STMW (< 400 m) intrudes through the gap westward because of the eddy transport, while the NPIW (800 m) is blocked by the Izu Ridge. Key Points: Erosion of the STMW trapped in AEs is revealed for the first time by special‐designed eddy‐tracking Argo profiles The lighter STMW in AEs dissipates quickly, but the denser STMW remains largely unchanged except when the AE passes across the Izu Ridge AEs transport STMW westward across the Izu Ridge through a bathymetric gap, but they cannot trap NPIW below the eddy trapped depth (600 m)